Animasi Propagule Journey dalam Meningkatkan Pemahaman Pelestarian Mangrove - Selly Artaty Zega; Aldian Husein; Maria (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2026)
Indonesia has the most extensive mangrove ecosystem in the world, but its condition is worsening due to a lack of environmental awareness and outdated teaching approaches. This research intends to create the Propagul Journey educational animation using the 4D model, which includes Define, Design, Develop, and Disseminate phases. During the Define stage, a knowledge gap was recognized and tackled using a "Show, Don't Tell" strategy in the Design phase. The Development phase incorporated parallax techniques to add depth, the Rubberhose 3 plug-in for flexible character animations, as well as Suno AI and Freesound for audio improvement. using an experimental design involving pre-test and post-test measurements within a single participant group. The findings indicated a notable increase in the participants' comprehension, rising from an average of 59. 2% to 83. 4%. Analysis shows that these outcomes strongly support the Define phase, where the visual and technical features designed effectively met the needs of the MAPALA audience. With a feasibility rating of 83. 4% deemed Very Valid, this animation successfully conveys complicated environmental topics in an understandable manner.